PELAKSANAAN UPAYA ADMINISTRATIF DAN IMPLIKASI YURIDISNYA TERHADAP PUTUSAN PENGADILAN TATA USAHA NEGARA - Yanuartanti, Anissa (Universitas Tadulako, 2025)
Even though administrative efforts as one of the benchmarks for the authority of the State Administrative Court in examining, deciding and resolving a case have been strictly regulated in regulations, there is still confusion among the public regarding its implementation. For example, the public is confused about the differences between administrative efforts in the basic regulations for publishing disputed objects and the provisions in the Law No. 30 of 2014. This research uses normative legal research methods with a statutory approach and a case approach. The results of the research show that there are fundamental differences between administrative efforts using basic regulations as intended in Article 48 of Law No. 5 of 1986 cand administrative efforts based on provisions in the Law No. 30 of 2014, namely in terms of procedures, time periods and the authority of the court which will adjudicate in cases where the public is dissatisfied with administrative effort decisions. Apart from that, the implementation of administrative measures has juridical implications for the decisions of state administrative courts, especially regarding the authority to adjudicate and the time limit for filing state administrative lawsuits Meskipun upaya administratif sebagai salah satu tolok ukur kewenangan Pengadilan Tata Usaha Negara telah diatur secara tegas dalam peraturan perundang-undangan, namun masih ditemukan kebingungan masyarakat dalam pelaksanaannya. Contohnya, masyarakat bingung mengenai perbedaan upaya administratif dalam peraturan dasar penerbitan objek sengketa dengan ketentuan dalam UU Administrasi Pemerintahan. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan undang-undang (statute approach) dan pendekatan kasus (case approach). Hasil penelitian menunjukkan bahwa terdapat perbedaan yang mendasar antara upaya administratif menggunakan peraturan dasar sebagaimana dimaksud dalam Pasal 48 UU PTUN dengan upaya administratif berdasarkan ketentuan dalam UU AP, yaitu dalam hal prosedur, jangka waktu, dan kewenangan pengadilan yang akan mengadili dalam hal masyarakat tidak puas dengan keputusan upaya administratif. Selain itu, pelaksanaan upaya administratif membawa implikasi yuridis terhadap putusan pengadilan tata usaha negara khususnya berkaitan dengan kewenangan mengadili serta tenggang waktu pengajuan gugatan tata usaha negara.